Physical activity and depression: Towards understanding the antidepressant mechanisms of physical activity - Kandola, Aaron; Ashdown-Franks, Garcia; Hendrikse, Joshua; Sabiston, Catherine M.; Stubbs, Brendon (Neuroscience and biobehavioral reviews, 2019)
•Engaging in physical activity can reduce depressive symptoms.•Exercise stimulates several neuroplastic processes implicated in depression.•It also reduces inflammation and increases resilience to oxidative and physiological stress.•Exercise promotes self-esteem, social support and self-efficacy.•Understanding these mechanisms can improve the design of exercise interventions and maximise treatment response. Physical activity can treat and prevent depressive symptoms, but its antidepressant mechanisms are yet to be established. In this review, we comprehensively assess key biological and psychosocial mechanisms through which physical activity exerts antidepressant effects, with a particular focus on exercise. Exercise, a subset of physical activity, influences a range of biological and psychosocial processes also implicated in the pathophysiology of depression. We focus on the capacity for exercise to elicit changes in neuroplasticity, inflammation, oxidative stress, the endocrine system, self-esteem, social support and self-efficacy. We also discuss how a better understanding of these mechanisms can inform the way we design and implement exercise-based interventions to maximise their antidepressant effects on an individual basis. We conclude by presenting a conceptual framework of the key biological and psychosocial mechanisms underlying the relationship between physical activity and depressive symptoms, and the moderators and confounders that may influence it.